Factores que determinan la informalidad en los comerciantes del mercado señor de los Milagros Contamana 2023 - Palacios Llerena, Beatriz Nicol (2024)
The main objective of this study was to identify the factors that determine informality among merchants in the Señor de los Milagros Market in Contamana in 2023. It was a basic research, at an explanatory level and with a non-experimental design. A sample of 182 merchants was taken, and the data was collected through a questionnaire using the survey technique. The results revealed that women and older merchants, especially those in the age group of 40 to 50 years, tend to present a higher degree of informality. On the other hand, a higher educational level is associated with lower levels of informality. In addition, the analysis determined that the economic factor explains approximately 56% of the variability in informality, which indicates that better economic conditions can foster this situation and evidences the need to implement interventions that promote a more regulated environment. Finally, cultural dynamics also turned out to be a significant factor, contributing to more than half of the variability in informality. This suggests that it is essential to consider the cultural aspect in order to address this phenomenon effectively.